Encyclopedist who has been ahead of his time (to the 125th anniversary of Yevhen Onatskyi’s birthday) - Serhii Bilokin (Енциклопедичний Вісник України, 2019)
The article is dedicated to Yevhen D. Onatskyi who is a prominent figure of Ukraine, primarily known as an encyclopedist because of The Small Ukrainian Encyclopedia that is his most famous work. The Small Ukrainian Encyclopedia was complied and published during his stay in exile in Argentina. The study reports that The Small Ukrainian Encyclopedia has finally been reprinted in Ukraine (4 volumes are planned to be published; currently 2 volumes (2016, 2018) are already issued). In 2019, it will be 125 years since the birth and 40 years since the death of Ye. D. Onatskyi.